Acupuncture management of metabolic-allergic eosinophilia: a single-patient case report - Soundarapandiyan, Sabeetha; L., Anto Princy; Krishnamurthy, Umadevi; Chidambaram, Yogapriya; Ravindran, Dhilip V. (International Journal of Research in Medical Sciences, 2026)
Eosinophilia is a heterogeneous condition associated with allergic, metabolic, or idiopathic etiologies and is often accompanied by systemic inflammatory manifestations. Integrative approaches such as acupuncture have been explored for their potential immunomodulatory and anti-inflammatory effects. This case report describes the clinical and laboratory outcomes of acupuncture as a sole therapeutic intervention in a patient with metabolic–allergic eosinophilia. A 57-year-old male with a history of hypertension presented with pruritic erythematous lesions on the right leg, persistent phlegm, throat congestion, mild breathlessness, and generalized heaviness. Laboratory investigations revealed mild eosinophilia, markedly elevated immunoglobulin E (IgE), increased high-sensitivity C-reactive protein (hs-CRP) and homocysteine levels, hyperuricemia, hypertriglyceridemia, and vitamin D deficiency. Clinical examination showed cutaneous inflammation and phlegm accumulation. Traditional Chinese Medicine assessment indicated a Phlegm-Damp pattern with Qi stagnation involving the lung-spleen-liver axis. The patient underwent a two-week acupuncture protocol as the sole treatment, targeting LI4, LI11, SP9, ST36, LU7, BL13, BL20, BL23, and LR3. No concurrent pharmacological or alternative therapies were administered. The acupuncture sessions were well tolerated, with no adverse events reported. Following treatment, the patient experienced significant symptomatic improvement, including a reduction in pruritus, improved respiratory comfort, decreased phlegm, better sleep quality, and enhanced overall well-being. Post-treatment laboratory findings demonstrated reductions in IgE levels (from 996 to 612 IU/mL), eosinophil percentage (from 7.8% to 5.6%), triglycerides, uric acid, hs-CRP, and homocysteine. This case suggests that acupuncture may be a safe and potentially effective supportive therapy for metabolic–allergic eosinophilia, contributing to symptomatic relief and improvements in inflammatory, immunological, and metabolic parameters. Further well-designed controlled studies with larger sample sizes are necessary to validate these findings and clarify underlying mechanisms.